The Effect of Leg Stretching Exercises with A Tennis Ball on Ankle Brachial Index as A Predictor of Diabetic Foot Ulcer - Yuliartini, Henny; Arwani, Arwani; Widiyanto, Budi (GLOBAL HEALTH SCIENCE GROUP, 2024)
Diabetic foot ulcers are caused by impaired peripheral circulation of the lower extremities due to peripheral arterial disease (PAD) that can be assessed by measuring the ankle brachial index. Leg stretching exercises with a tennis ball have an effect on increasing ABI values and predict the incidence of diabetic foot ulcers. Objective : This stydy aims to improve the effect of leg stretching exercises with a tennis ball on the ABI value as a predictor of the incidence of diabetic foot ulcers. Method: Quasi experimental quantitative research with a pretest-posttest with control group design. The total sample was 46 respondents using a purposive sampling technique to determine the Intervention group and Control group in 2 Puskesmas work areas that have plenary accreditation. After selecting each group, identification was carried out according to the inclusion criteria and exclusion criteria, resulting in 23 respondents in the Intervention group and 23 respondents in the Control group. The intervention group was given leg stretching exercises with a tennis ball for 15 minutes 14 times in 2 weeks and the control group received treatment from the Community Health Center, namely PROLANIS exercises. Data analysis uses univariate analysis and bivariate analysis, Paired Sample t-Test and Independent t-Test. Results: The ankle brachial index average increased to 0,300 mmHg and the prediction of the incidence of foot ulcers were decreased on the Intervention group (p=0,000) wheras the Control group ankle brachial index average decreased to 0,082 mmHg and the prediction of the incidence of foot ulcers were increased (p=0,008). Conclusion: Leg stretching exercises with a tennis ball have an effect on increasing ankle brachial index and can be used as a predictor of diabetic foot ulcers in type 2 diabetes mellitus.